Design and commissioning of a virtual image solar simulator for testing thermal collectors. (1st January 2018) - Moss, R.W.; Shire, G.S.F.; Eames, P.C.; Henshall, P.; Hyde, T.; Arya, F.
Highlights: An internally reflecting light tube increases illumination level and uniformity. The measured illumination level was 2.3% higher than predicted. Floodlight infra-red emissions raise cover glass temperature. Cooling fan brings collector efficiency within 1% of AM1.5 spectrum equivalent. Abstract: A solar simulator has been designed and built for testing prototype (0.5 × 0.5 m) flat plate thermal collectors. An internally reflecting light tube generates multiple virtual images of the four halogen floodlights to ensure uniform illumination. Ray-tracing simulations were used to choose the tube dimensions and maximum allowable clearance. Illumination measurements agree well with these predictions. The visible & near IR spectrum appears to follow a black body curve. In the absence of a "cold sky" IR filter there is a secondary, long wavelength IR spectral component that causes heating of the cover glass on a solar flat plate collector. The cover glass temperature can be maintained at typical outdoor levels using a cooling fan. The design would be well suited to LED illumination. Simulation of solar collector response to this spectrum shows that an efficiency based on pyranometer readings is approximately 1% higher than would be obtained with an AM1.5 spectrum.